ANALISIS PEMILIHAN APLIKASI REPOSITORI PUBLIKASI ILMIAH BADAN PENELITIAN DAN PENGEMBANGAN PERTANIAN - Henriyadi, Henriyadi (Informatika Pertanian, 2012)
One ferm of scientific recognition indicators for research institution is the number of research articles in scientific publications (journals, proceedings) whether printed or digital form. Scientific publications are usually available in digital format and as a link to the website of each research center as publisher of the publication. Problems that occur with the digital form of scientific publications are difficulties for users to find information, because they have to search them on each research center web sites to obtain the topic. The study chose the appropriate application to integrate the scattered scientific publications into an Institutional Repository, therefore of the user would be easier to trace information and increased Indonesian Agency for Agricultural Research and Development (IAARD) scientific recognition. The method for selecting was adapted and modified from COTS-software-product framework and Analytical Hierarchy Process (AHP) multi criteria analysis. The result indicated that the best application for Repository IAARD scientific publication is DSpace Software.